1998
DOI: 10.1200/jco.1998.16.2.495
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of vitamin E for hot flashes in breast cancer survivors.

Abstract: Although this trial was able to show a statistically significant hot flash reduction with vitamin E compared to a placebo, the clinical magnitude of this reduction was marginal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(142 citation statements)
references
References 13 publications
1
135
0
6
Order By: Relevance
“…In examining symptom management for hot fl ashes used by 74 women, they reported using vitamins (51%), exercise (23%), nonhormonal medications (16%), diet (15%), and behavioral methods (14%) (Carpenter et al). Vitamin E was found to decrease hot fl ashes minimally in breast cancer survivors (Barton et al, 1998). The use of soy supplementation remains controversial, with limited evidence showing that dietary soy relieves hot fl ashes.…”
Section: Use Of Complementary and Alternative Medicine For Symptom Mamentioning
confidence: 99%
“…In examining symptom management for hot fl ashes used by 74 women, they reported using vitamins (51%), exercise (23%), nonhormonal medications (16%), diet (15%), and behavioral methods (14%) (Carpenter et al). Vitamin E was found to decrease hot fl ashes minimally in breast cancer survivors (Barton et al, 1998). The use of soy supplementation remains controversial, with limited evidence showing that dietary soy relieves hot fl ashes.…”
Section: Use Of Complementary and Alternative Medicine For Symptom Mamentioning
confidence: 99%
“…However, many of these therapies have shown marginal, or no, benefit. For example, a placebo-controlled, randomized trial involving the use of vitamin E demonstrated that vitamin E administration resulted in a minimal decrease in hot flashes and was not preferred over placebo [43,55]. Additionally, placebo-controlled trials investigating soy phytoestrogen and black cohosh found no significant benefit from these agents [43,56].…”
Section: Complementary and Alternative Medicine Approachesmentioning
confidence: 99%
“…Estrogenic exposures come in many forms, including plant and environmental estrogens (Hilakivi- Clarke et al, 1999b;Clarke et al, 2001a), dietary exposures that affect the levels of endogenous estrogens (Hilakivi-Clarke et al, 1997), and estrogenic HRT (Clarke et al, 2001b). Dietary antioxidant exposure also may affect antiestrogen responsiveness (Clarke et al, 2001b) and some women already take the most potent natural antioxidant (vitamin E) as an alternative medicine for controlling menopausal symptoms (Stampfer et al, 1993;Barton et al, 1998;Koh et al, 1999).…”
Section: Exogenous Estrogenic Exposures and Their Effects On Antiestrmentioning
confidence: 99%